Salmonella chronic carriage: epidemiology, diagnosis and gallbladder persistence - Gunn, John S. (Trends Microbiol, 2014)
Typhoid (enteric fever) remains a major cause of morbidity and mortality worldwide, causing over 21 million new infections annually, with the majority of deaths occurring in young children. As typhoid fever-causing Salmonella have no known environmental reservoir, the chronic, asymptomatic carrier state is thought to be a key feature of continued maintenance of the bacterium within human populations. In spite of the importance of this disease to public health, our understanding of the molecular mechanisms that catalyze carriage, as well as our ability to reliably identify and treat the Salmonella carrier state, have only recently begun to advance.